An Examination of Gender Balance in ICT at Educational Institutions - The Research Unit Policy Planning Development and Evaluation Division (The Research Unit Policy Planning Development and Evaluation Division, 2018)
The Information and Communication Technology (ICT) Division within the Ministry of Science and Technology (MST) is in the process of reviewing the national ICT Policy for Jamaica. The Research Unit was asked to assist with determining how gender is balanced in Jamaica’s ICT sector, with particular focus on the education system. The rationale being to determine if there is indeed a gender disparity that needs to be addressed in the revised policy. On that basis, the Unit examined enrolment and graduation data disaggregated by gender for the following educational institutions/levels: 1. Secondary Schools: Students enrolled in CSEC1 Information Technology (IT) and number of students with passes at Grades I – III. 2. University of the West Indies (UWI): Department of Computing. 3. University of Technology (UTECH): School of Computing and Information Technology (SCIT) 4. Northern Caribbean University (NCU): Department of Computing and Information Sciences 5. Vocational Training Development Institute (VTDI): BSc in Information and Communications Technology 6. Scientific Research Council: Information on National Innovation Awards